ANALISIS EKONOMI DAN NON EKONOMI USAHA BUDIDAYA UDANG VANAME (Litopenaeus vannamei) SKALA RUMAH TANGGA DI POKDAKAN MIKRO BIO EBI AIR MAWAR PANGKALPINANG - Nur Rahmadina; Endang Bidayani; Ahmad Fahrul Syarif (Journal of Fish Nutrition, 2022)
Aquaculture is an aquaculture activity to produce aquatic biota in a controlled environment so as to gain profits and is a sustainable activity that must be developed further. One of the aquaculture activities is vaname shrimp cultivation. This activity, especially brackish water cultivation, has developed in the community, especially in Bangka Belitung Province, but before starting a business, it is necessary to conduct a business analysis to see the feasibility of the business being carried out. So it is necessary to analyze the vannamei shrimp cultivation business in Pokdakan Micro Bio Ebi Air Mawar. This research was conducted in January 2022 in Air Mawar Village, Pangkalpinang City. This research uses a descriptive survey method in the form of a case study method in determining non-economic analysis and a business feasibility test is carried out with a case study method in analyzing aquaculture business. The business analysis was carried out in the vannamei shrimp rearing pond. Pokdakan Micro Bio Ebi Rose Water. The results showed that the non-economic analysis has good marketing, good environmental management, good water quality, and has completed a Uzaha license and has a strategic place for the development of vaname shrimp cultivation so that production activities take place well. Methods of data processing analysis of vannamei shrimp enlargement business. Pokdakan Mikro Bio Ebi Air Mawar uses a quantitative method. The results showed that seen from the results of the cycle calculation resulted in an income of Rp. 172.800,000, profit Rp. 100.450,000, and the R/C Ratio value of 2,38, Payback Period of 0,47 years, Break Event Product sales of 753,64 Kg, and Break Event Point Price is Rp.40.194. Based on this, the household scale vaname shrimp enlargement business in Pokdakan Mikro Bio Ebi is feasible to be developed.